Defining patient‐centered research priorities in pediatric dermatology. Issue 2 (28th November 2022) - Neale, Holly; Schrandt, Suz; Abbott, Becky M.; Austin, Jennifer; Brand, Callista; Camp, Karen; Devenport, Katherine; Hall, Michelle; Isbell, Lauren; Miciano, Charlene; Pry, Sarah; Quinn, Paula; et al.
Abstract: Background/Objectives: Patient and caregiver perspectives are critical in understanding dermatologic disease impact, presentation, and management in children. The Pediatric Dermatology Research Alliance (PeDRA) Patient Advisory Committee (PtAC), a group of patient representatives and parents of children with cutaneous disease, pursued a multistep, iterative, consensus‐building process to identify comprehensive, high‐priority research needs. Methods: Building on discussions at the 2020 PeDRA Annual Conference, a research prioritization survey was developed and completed by PtAC members. Survey themes were aggregated and workshopped by the PtAC through a series of facilitated calls. Emerging priorities were refined in collaboration with additional PeDRA patient community members at the 2021 PeDRA Annual Conference. Subsequently, a final actionable list was agreed upon. Results: Fourteen PtAC members (86.7% female) representing patients with alopecia areata, atopic dermatitis, vascular birthmarks, congenital melanocytic nevi, ectodermal dysplasias, epidermolysis bullosa, Gorlin syndrome, hidradenitis suppurativa, ichthyosis, pemphigus, psoriasis, Sturge–Weber syndrome, and pachyonychia congenita completed the survey. Following serial PtAC meetings, 60 research needs were identified from five domains: psychosocial challenges, health care navigation/disease management, causes/triggers, treatments to preserve or save life, and treatments to preserve or save quality of life. Conclusions: Many pediatric dermatology research priorities align across affected communities and may drive meaningful, patient‐centric initiatives and investigations.